Difference between revisions of "2016 USAMO Problems/Problem 4"
(Created page with "== Problem == Find all functions <math>f:\mathbb{R}\rightarrow \mathbb{R}</math> such that for all real numbers <math>x</math> and <math>y</math>, <cmath>(f(x)+xy)\cdot f(x-3y...") |
|||
Line 4: | Line 4: | ||
== Solution == | == Solution == | ||
− | Step 1: Set <math>x = y = 0</math> to obtain <math>f(0) = 0.</math> | + | '''Step 1:''' Set <math>x = y = 0</math> to obtain <math>f(0) = 0.</math> |
− | Step 2: Set <math>x = 0</math> to obtain <math>f(y)f(-y) = f(y)^2.</math> | + | '''Step 2:''' Set <math>x = 0</math> to obtain <math>f(y)f(-y) = f(y)^2.</math> |
<math>\indent</math> In particular, if <math>f(y) \ne 0</math> then <math>f(y) = f(-y).</math> | <math>\indent</math> In particular, if <math>f(y) \ne 0</math> then <math>f(y) = f(-y).</math> | ||
Line 12: | Line 12: | ||
<math>\indent</math> In addition, replacing <math>y \to -t</math>, it follows that <math>f(t) = 0 \implies f(-t) = 0</math> for all <math>t \in \mathbb{R}.</math> | <math>\indent</math> In addition, replacing <math>y \to -t</math>, it follows that <math>f(t) = 0 \implies f(-t) = 0</math> for all <math>t \in \mathbb{R}.</math> | ||
− | Step 3: Set <math>x = 3y</math> to obtain <math>\left[f(y) + 3y^2\right]f(8y) = f(4y)^2.</math> | + | '''Step 3:''' Set <math>x = 3y</math> to obtain <math>\left[f(y) + 3y^2\right]f(8y) = f(4y)^2.</math> |
<math>\indent</math> In particular, replacing <math>y \to t/8</math>, it follows that <math>f(t) = 0 \implies f(t/2) = 0</math> for all <math>t \in \mathbb{R}.</math> | <math>\indent</math> In particular, replacing <math>y \to t/8</math>, it follows that <math>f(t) = 0 \implies f(t/2) = 0</math> for all <math>t \in \mathbb{R}.</math> | ||
− | Step 4: Set <math>y = -x</math> to obtain <math>f(4x)\left[f(x) + f(-x) - 2x^2\right] = 0.</math> | + | '''Step 4:''' Set <math>y = -x</math> to obtain <math>f(4x)\left[f(x) + f(-x) - 2x^2\right] = 0.</math> |
<math>\indent</math> In particular, if <math>f(x) \ne 0</math>, then <math>f(4x) \ne 0</math> by the observation from Step 3, because <math>f(4x) = 0 \implies f(2x) = 0 \implies f(x) = 0.</math> Hence, the above equation implies that <math>2x^2 = f(x) + f(-x) = 2f(x)</math>, where the last step follows from the first observation from Step 2. | <math>\indent</math> In particular, if <math>f(x) \ne 0</math>, then <math>f(4x) \ne 0</math> by the observation from Step 3, because <math>f(4x) = 0 \implies f(2x) = 0 \implies f(x) = 0.</math> Hence, the above equation implies that <math>2x^2 = f(x) + f(-x) = 2f(x)</math>, where the last step follows from the first observation from Step 2. | ||
Line 24: | Line 24: | ||
<math>\indent</math> Looking back on the equation from Step 3, it follows that <math>f(y) + 3y^2 \ne 0</math> for any nonzero <math>y.</math> Therefore, replacing <math>y \to t/4</math> in this equation, it follows that <math>f(t) = 0 \implies f(2t) = 0.</math> | <math>\indent</math> Looking back on the equation from Step 3, it follows that <math>f(y) + 3y^2 \ne 0</math> for any nonzero <math>y.</math> Therefore, replacing <math>y \to t/4</math> in this equation, it follows that <math>f(t) = 0 \implies f(2t) = 0.</math> | ||
− | Step 5: If <math>f(a) = f(b) = 0</math>, then <math>f(b - a) = 0.</math> | + | '''Step 5:''' If <math>f(a) = f(b) = 0</math>, then <math>f(b - a) = 0.</math> |
<math>\indent</math> This follows by choosing <math>x, y</math> such that <math>x - 3y = a</math> and <math>3x - y = b.</math> Then <math>x + y = \tfrac{b - a}{2}</math>, so plugging <math>x, y</math> into the given equation, we deduce that <math>f\left(\tfrac{b - a}{2}\right) = 0.</math> Therefore, by the third observation from Step 4, we obtain <math>f(b - a) = 0</math>, as desired. | <math>\indent</math> This follows by choosing <math>x, y</math> such that <math>x - 3y = a</math> and <math>3x - y = b.</math> Then <math>x + y = \tfrac{b - a}{2}</math>, so plugging <math>x, y</math> into the given equation, we deduce that <math>f\left(\tfrac{b - a}{2}\right) = 0.</math> Therefore, by the third observation from Step 4, we obtain <math>f(b - a) = 0</math>, as desired. | ||
− | Step 6: If <math>f \not\equiv 0</math>, then <math>f(t) = 0 \implies t = 0.</math> | + | '''Step 6:''' If <math>f \not\equiv 0</math>, then <math>f(t) = 0 \implies t = 0.</math> |
<math>\indent</math> Suppose by way of contradiction that there exists an nonzero <math>t</math> with <math>f(t) = 0.</math> Choose <math>x, y</math> such that <math>f(x) \ne 0</math> and <math>x + y = t.</math> The following three facts are crucial: | <math>\indent</math> Suppose by way of contradiction that there exists an nonzero <math>t</math> with <math>f(t) = 0.</math> Choose <math>x, y</math> such that <math>f(x) \ne 0</math> and <math>x + y = t.</math> The following three facts are crucial: | ||
Line 39: | Line 39: | ||
<math>\indent</math> By the second observation from Step 4, these three facts imply that <math>f(y) = y^2</math> and <math>f(x - 3y) = \left(x - 3y\right)^2</math> and <math>f(3x - y) = \left(3x - y\right)^2.</math> By plugging into the given equation, it follows that | <math>\indent</math> By the second observation from Step 4, these three facts imply that <math>f(y) = y^2</math> and <math>f(x - 3y) = \left(x - 3y\right)^2</math> and <math>f(3x - y) = \left(3x - y\right)^2.</math> By plugging into the given equation, it follows that | ||
− | \begin{align*} | + | <cmath>\begin{align*} |
\left(x^2 + xy\right)\left(x - 3y\right)^2 + \left(y^2 + xy\right)\left(3x - y\right)^2 = 0. | \left(x^2 + xy\right)\left(x - 3y\right)^2 + \left(y^2 + xy\right)\left(3x - y\right)^2 = 0. | ||
− | \end{align*}But the above expression miraculously factors into <math>\left(x + y\right)^4</math>! This is clearly a contradiction, since <math>t = x + y \ne 0</math> by assumption. This completes Step 6. | + | \end{align*}</cmath> But the above expression miraculously factors into <math>\left(x + y\right)^4</math>! This is clearly a contradiction, since <math>t = x + y \ne 0</math> by assumption. This completes Step 6. |
− | Step 7: By Step 6 and the second observation from Step 4, the only possible solutions are <math>f \equiv 0</math> and <math>f(x) = x^2</math> for all <math>x \in \mathbb{R}.</math> It's easy to check that both of these work, so we're done. | + | '''Step 7:''' By Step 6 and the second observation from Step 4, the only possible solutions are <math>f \equiv 0</math> and <math>f(x) = x^2</math> for all <math>x \in \mathbb{R}.</math> It's easy to check that both of these work, so we're done. |
{{MAA Notice}} | {{MAA Notice}} |
Revision as of 16:10, 21 April 2016
Problem
Find all functions such that for all real numbers
and
,
Solution
Step 1: Set to obtain
Step 2: Set to obtain
In particular, if
then
In addition, replacing
, it follows that
for all
Step 3: Set to obtain
In particular, replacing
, it follows that
for all
Step 4: Set to obtain
In particular, if
, then
by the observation from Step 3, because
Hence, the above equation implies that
, where the last step follows from the first observation from Step 2.
Therefore, either
or
for each
Looking back on the equation from Step 3, it follows that
for any nonzero
Therefore, replacing
in this equation, it follows that
Step 5: If , then
This follows by choosing
such that
and
Then
, so plugging
into the given equation, we deduce that
Therefore, by the third observation from Step 4, we obtain
, as desired.
Step 6: If , then
Suppose by way of contradiction that there exists an nonzero
with
Choose
such that
and
The following three facts are crucial:
1.
This is because
, so by Step 5,
, impossible.
2.
This is because
, so by Step 5 and the observation from Step 3,
, impossible.
3.
This is because by the second observation from Step 2,
Then because
, Step 5 together with the observation from Step 3 yield
, impossible.
By the second observation from Step 4, these three facts imply that
and
and
By plugging into the given equation, it follows that
But the above expression miraculously factors into
! This is clearly a contradiction, since
by assumption. This completes Step 6.
Step 7: By Step 6 and the second observation from Step 4, the only possible solutions are and
for all
It's easy to check that both of these work, so we're done.
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.
See also
2016 USAMO (Problems • Resources) | ||
Preceded by Problem 3 |
Followed by Problem 5 | |
1 • 2 • 3 • 4 • 5 • 6 | ||
All USAMO Problems and Solutions |
2016 USAJMO (Problems • Resources) | ||
Preceded by Problem 5 |
Last Problem | |
1 • 2 • 3 • 4 • 5 • 6 | ||
All USAJMO Problems and Solutions |